الفكر التحرّري عند الشيخ عبد العزيز الثّعالبي وأبعاده الوطنيّة والقوميّة - هاشم, كوثر; عقيب, محمد السعيد (جامعة الوادي - University of Eloued, 2018)
دافع عبد العزيز الثّعالبي طيلة مسيرته النّضاليّة عن تحرّر وطنه تونس، وسائر بلاد العرب والمسلمين، فكان صوتها المدوّي المناهض للهيمنة الاستعماريّة مطالبا بحق الاستقلال واسترجاع كرامة التّونسيّين التي سلبت منهم، ورأى أنّ سبيل ذلك إنّما يكون بالتخلّص التّام من الاستعمار منطلقا في ذلك من معاداته له، وضرورة إصلاح الفرد والمجتمع التّونسي والعربي والإسلامي في شتّى المجالات، متمسّكا بمقوّمات الوطنيّة الثّلاث الإسلام – اللغة العربيّة – التّاريخ المشترك بين الشّعوب المغاربيّة والعربيّة والإسلامية مؤكّدا على وحدتها واتّحادها . وقد كان لفكر الثّعالبي ومبادئه التحرّريّة تأثيره ليس على مستوى السّاحة الوطنيّة التّونسيّة فحسب، وإنّما وصلت أفكاره وجهوده إلى نصرة مختلف البلدان العربيّة والإسلاميّة، وقاوم معها ضدّ الاستعمار الأوربيّ. Abstract: Abdelaziz Thâalbi defended throughout his struggle for the liberation of his native Tunisia, and other Arab and Muslim countries, and her voice was resounding anti-colonial domination, demanding the right to independence and recover the dignity of Tunisians who robbed them, and that to this end it will be the total elimination of colonialism, the starting point in that of antagonism to him and the need to Tunisian reform of the individual and the community and the Arab and Muslim in various fields, stick to the three national viable (Islam - Arabic language - a common history) between the Maghreb and the Arab and Islamic peoples, stressing their unity and union. He was thought Thaalbi and principles of liberal influence not only on the level of the Tunisian national scene, but got his ideas and his efforts to support the various Arab and Islamic countries, and fought with them against European colonialism.
مقال
Keywords: الثعالبي، تونس، النخبة